2020
DOI: 10.1038/s41598-020-57863-5
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomics, in-silico evaluation and immunoblotting assays for allergenicity assessment of lesser mealworm, black soldier fly and their protein hydrolysates

Abstract: Since 2018, insects have belonged the category of Novel Foods and the presence of allergens represents one of the main hazards connected to their consumption, also due to the potential cross-reactivity with Arthropoda pan-allergens. In the present work, the allergenicity assessment of black soldier fly and lesser mealworm was performed with a shotgun bottom-up proteomic approach combined with in-silico assessment, followed by IgG-and IgE-immunoblotting experiments. The peptides identified, filtered for their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Recent publications demonstrated cross-reactivity between edible insects and other Arthropoda (crustaceans, mite), identifying different proteins that are involved in muscle contraction (actin, myosin, tropomyosin, troponin T and C, tubulin), in enzymatic pathways (arginine kinase 1, alpha-amylase) or part of the hemolymphatic system (hexamerin 1 and 2) as pan-allergens [48]. Globally, the results that are presented in Table 1 showed that pepsin was more efficient than Alcalase ® for hydrolysis of allergenic mealworm proteins, despite the fact that, on the whole, the DH that was obtained with Alcalase ® was higher ( Figure 2).…”
Section: Digestion Of Mealworm Allergenic Proteins By Pressurization mentioning
confidence: 99%
“…Recent publications demonstrated cross-reactivity between edible insects and other Arthropoda (crustaceans, mite), identifying different proteins that are involved in muscle contraction (actin, myosin, tropomyosin, troponin T and C, tubulin), in enzymatic pathways (arginine kinase 1, alpha-amylase) or part of the hemolymphatic system (hexamerin 1 and 2) as pan-allergens [48]. Globally, the results that are presented in Table 1 showed that pepsin was more efficient than Alcalase ® for hydrolysis of allergenic mealworm proteins, despite the fact that, on the whole, the DH that was obtained with Alcalase ® was higher ( Figure 2).…”
Section: Digestion Of Mealworm Allergenic Proteins By Pressurization mentioning
confidence: 99%
“…They grow and reproduce easily, have low feed conversion rate compared to conventional livestock animals (one kg of insect biomass can be produced from 1.7 Kg of feed biomass, depending on species) and can be reared on agro-industrial by-products [ 3 , 4 ]. In addition to serving as feed, insects provide a high nutritional profile for humans, although the presence of allergens represents a potential hazards that must be further investigated [ 5 , 6 ]. Overall, it is demonstrated that insects production involves low energy, land area utilization and environmental footprints [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hall and colleagues have demonstrated that hydrolyzing cricket proteins with alcalase reduced tropomyosin Immunoglobulin E (IgE) reactivity in shrimp allergic patients and that hydrolyzing the proteins even further to 60% to 85% degree of hydrolysis completely reduced the IgE reactivity to tropomyosin. Hydrolyzing BSFL proteins showed a reduction in immune reactivity, but there was partial preservation of IgE reactivity (Leni et al, 2020b), although with further research this could be a technique that could be used to reduce allergic reactions caused by BSFL proteins completely.…”
Section: Allergen Risksmentioning
confidence: 95%
“…Arginine kinase, found in many varieties of prawn species, has been found in the lesser mealworm (Alphitobius diaperinus) (Leni et al, 2020b), field cricket (Gryllus bimaculatus), silkworm larvae (Bombyx mori) (Liu et al, 2011), the German cockroach (Blattella germanica) (Chuang, Su, Chiang, Lee, & Chow, 2010), and the Indian meal moth (Plodia interpunctella). In a shotgun proteomics study, arginine kinase was not identified as a major pan allergen in BSFL (Leni et al, 2020b); however, Broekman et al (2017) identified the presence of arginine kinase in BSFL protein extract. Tropomyosin and arginine kinase are declared allergens for Arthropoda in the Allergen Nomenclature database (http://www.allergen.org/index.php) and have been found in both crustacean species and insect species.…”
Section: Allergen Risksmentioning
confidence: 99%